Impact assessment of IFPRI’s capacity-strengthening work, 1985–2010: Synopsis - Kuyvenhoven, Arie (International Food Policy Research Institute, 2014)
Strengthening national capacities for undertaking, communicating, and using evidence-based food policy analysis has long been one of IFPRI’s objectives. IFPRI has therefore engaged in various forms of capacity strengthening (CS), including formal training, collaborative research and outreach, and institutional development. CS has also been delivered through individual projects, country programs, regional networks, and thematic multicountry programs.